Groundsel man - H.G. Hine; E. Whimpers (Tufts Archival Research Center, 2008)
This illustration is from Henry Mayhew's "London Labour and the London Poor" v.1. Caption reads: "Chick-weed and grun-sell!" From a daguerreotype by Beard.